Efficacy of herpes virus helicase-primase inhibitor, ASP2151, for treating herpes simplex keratitis in mouse model. Issue 4 (29th January 2013) - Sasaki, Shin-Ichi; Miyazaki, Dai; Haruki, Tomoko; Yamamoto, Yukimi; Kandori, Michiko; Yakura, Keiko; Suzuki, Hiroshi; Inoue, Yoshitsugu
Abstract : Aims: To determine the efficacy of a new helicase-primase inhibitor, ASP2151, for treating herpetic keratitis. Methods: Murine corneas were infected with herpes simplex virus type 1 (HSV-1). ASP2151 was administered orally or topically, and the severity of epithelial dendritic keratitis was determined. The effectiveness of ASP2151 was compared with that of acyclovir and valacyclovir. The reduction of the amount of HSV in tears, enucleated eyes and trigeminal ganglia was determined by real-time PCR or plaque assay. Results: Orally administered ASP2151 reduced the epithelial keratitis score significantly more than that of the vehicle-treated group (p<0.01). It also lowered the HSV-DNA levels in the tears significantly more than that by valacyclovir (p<0.01). ASP2151 ointment resulted in the same reduction of the keratitis score as acyclovir ointment, and lowered the HSV DNA in tears more than acyclovir ointment. Topical instillation of ASP2151 improved the herpetic dendritic keratitis score significantly and reduced the titre of HSV DNA in the tears in a dose-responsive way. Conclusions: ASP2151 had significantly better anti-HSV activity against herpes simplex keratitis than valacyclovir and acyclovir after systemic or topical use. These findings indicate that ASP2151 should be considered as an alternative treatment for herpes simplex keratitis.